Rancang Bangun Website TK-SD Pada Fluency Kids Di Kota Pagar Alam - Evy Septriani; Yeni yeni (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2016)
The purpose of this study is the Build website at SMP Negeri 3 Kota Pagar Alam in order to help users get information about the activities of student learning, teaching, school achievement, teachers and students. With her website at SMP Negeri 3 Kota Pagar Alam is expected to provide fast, precise and accurate for those in need. Currently in SMP Negeri 3 Kota Pagar Alam despite the availability of the Internet however, the unavailability of a website to facilitate the search of information about SMP Negeri 3 Kota Pagar Alam. Systems Development Method used method of Web Engineering with stage-phases: Custumer Communication, Planning, Modeling, Contruction and Deployment. Design using UML and Programming using PHP. The results of the research available Fluency Kids Website Pagar Alam Alam can be accessed by the user wanted to know information Kids Fluency Pagar Alam.